Rapid Screening for Cognitive Impairment in Parkinson's Disease: A Pilot Study. (2nd December 2015) - Dong, YanHong; Koay, Way Inn; Yeo, Leonard Leong Litt; Chen, Christopher Li-Hsian; Xu, Jing; Seet, Raymond Chee Seong; Lim, Erle Chuen Hian
Abstract : Aim . This study sought to establish the discriminant validity of a rapid cognitive screen, that is, the National Institute of Neurological Disease and Stroke-Canadian Stroke Network (NINDS-CSN) 5-minute protocol, and compare its discriminant validity to the Montreal Cognitive Assessment (MoCA) and Mini Mental State Examination (MMSE) in detecting cognitive impairment (CI) in PD patients. Methods . One hundred and one PD patients were recruited from a movement disorders clinic in Singapore and they received the NINDS-CSN 5-minute protocol, MoCA, and MMSE. No cognitive impairment (NCI) was defined as Clinical Dementia Rating (CDR) = 0 and CI was defined as CDR ≥ 0.5. Results . Area under the receiver operating characteristic curve of NINDS-CSN 5-minute protocol was statistically equivalent to MoCA and larger than MMSE (0.86 versus 0.90, P = 0.07 ; 0.86 versus 0.76, P = 0.03 ). The sensitivity of NINDS-CSN 5-minute protocol (<9) was statistically equivalent to MoCA (<22) (0.77 versus 0.85, P = 0.13 ) and superior to MMSE (<24) (0.77 versus 0.52, P < 0.01 ) in detecting CI, while the specificity of NINDS-CSN 5-minute protocol (<9) was statistically equivalent to MoCA (<22) and MMSE (<24) (0.78 versus 0.88, P = 0.34 ). Conclusion . The NINDS-CSN 5-minute protocol is time expeditious while remaining statistically equivalent to MoCA and superior to MMSE and therefore is suitable for rapid cognitive screening of CI in PD patients.